Evidence of insecticide resistance selection in wild Anopheles coluzzii mosquitoes due to agricultural pesticide use - Chouaïbou Seïdou Mouhamadou; Sarah Souline de Souza; Behi Kouadio Fodjo; Marius Gonse Zoh; Nestor Kesse Bli; Benjamin Guibehi Koudou (BMC, 2019)
Abstract Background The wetlands used for some agricultural activities constitute productive breeding sites for many mosquito species. Thus, the agricultural use of insecticide targeting other pests may select for insecticide resistance in malaria mosquitoes. The purpose of this study is to clarify some knowledge gaps on the role of agrochemicals in the development of insecticide resistance in malaria vectors is of utmost importance for vector control. Methods Using the CDC bottle test and the log-probit analysis, we investigated for the first time the resistance levels of Anopheles coluzzii mosquitoes to neonicotinoids, insecticides used exclusively for crop protection in Côte d'Ivoire. The study was conducted in two agricultural regions (Tiassale and Gagnoa) and one non-agricultural region (Vitre) between June and August 2017 using clothianidin, acetamiprid and imidacloprid. Results Mosquito populations from Tiassale and Gagnoa (agricultural settings) were determined to be resistant to acetamiprid with mortality rates being < 85% at 24 h post-exposure. In Vitre (non-agricultural area) however, the mosquito population was susceptible to acetamiprid. In all three localities, mosquito populations were resistant to imidacloprid (mortality rates were 60% in Vitre, 37% in Tiassale, and 13% in Gagnoa) and completely susceptible to clothianidin (100% mortality). An. coluzzii represented 100% of mosquito collected in Gagnoa, 86% in Tiassale and 96% in Vitre. Conclusions This study provides strong evidence that agricultural use of insecticides can cause insecticide resistance in malaria vector populations. Insecticide resistance driven by agrochemical usage should be considered when vector control strategies are developed.